A polymorphism at position 400 in the connection subdomain of HIV-1 reverse transcriptase affects sensitivity to NNRTIs and RNaseH activity. - David W Wright; Ilona P Deuzing; Philippe Flandre; Peter van den Eede; Micheline Govaert; Laurentia Setiawan; Peter V Coveney; Anne-Geneviève Marcelin; Vincent Calvez; Charles A B Boucher; Nancy Beerens (PLoS ONE)
Reverse transcriptase (RT) plays an essential role in HIV-1 replication, and inhibition of this enzyme is a key component of HIV-treatment. However, the use of RT inhibitors can lead to the emergence of drug-resistant variants. Until recently, most clinically relevant resistance mutations were found in the polymerase domain of RT. Lately, an increasing number of resistance mutations has been identified in the connection and RNaseH domain. To further explore the role of these domains we analyzed the complete RT sequence of HIV-1 subtype B patients failing therapy. Position A/T400 in the connection subdomain is polymorphic, but the proportion of T400 increases from 41% in naïve patients to 72% in patients failing therapy. Previous studies suggested a role for threonine in conferring resistance to nucleoside RT inhibitors. Here we report that T400 also mediates resistance to non-nucleoside RT inhibitors. The susceptibility to NVP and EFV was reduced 5-fold and 2-fold, respectively, in the wild-type subtype B NL4.3 background. We show that substitution A400T reduces the RNaseH activity. The changes in enzyme activity are remarkable given the distance to both the polymerase and RNaseH active sites. Molecular dynamics simulations were performed, which provide a novel atomistic mechanism for the reduction in RNaseH activity induced by T400. Substitution A400T was found to change the conformation of the RNaseH primer grip region. Formation of an additional hydrogen bond between residue T400 and E396 may play a role in this structural change. The slower degradation of the viral RNA genome may provide more time for dissociation of the bound NNRTI from the stalled RT-template/primer complex, after which reverse transcription can resume.